Roman Invaders and Settlers - Marsden, Barry M. (Hove Wayland, 1992)
Another title from the INVADERS AND SETTLERS series, with colour photographs, maps and artwork to illustrate a study of the Romans, who they were, why they invaded and settled in Britain, their way of life, and the legacy of their invasion. Meets the requirements of the National Curriculum Key Stage 2
Include Color Illustration and Index
Keywords: Great Britain -- Romans